Overview on brain function enhancement of Internet addicts through exercise intervention: Based on reward-execution-decision cycle - Chen, Hao; Dong, Guijun; Li, Kefeng (Frontiers in Psychiatry, 2023)
Internet addiction has become an impulse control disorder included in the category of psychiatric disorders. Especially after the outbreak of the new crown epidemic, there has been a surge trend of Internet addiction. Internet addiction damages some brain functions in humans. Emerging evidence suggests exercise exerts beneficial effects on brain function and cognitive level damaged by Internet addiction. This paper reviews the neurobiological mechanisms of Internet addiction and describes the impairment of brain function by Internet addiction from three systems: reward, execution, and decision-making. Furthermore, we sort out the research related to exercise intervention on Internet addiction and its impact on improving brain function. It is important to consider the internal and external factors that produce Internet addiction when summarizing movement interventions from a behavioral perspective. We can design exercise prescriptions based on exercise interests and then achieve the goal of quitting Internet addiction. This paper explores the possible mechanisms of exercise to improve Internet addiction through systematic analysis. It provides research directions for the future targeted design of exercise prescriptions.